O64 Improving teamworking & leadership in mulitidsiciplinary ad-hoc teams. (5th November 2017) - Geraghty, A; Adamson, J; Dhasmana, D; Bennett, C
Abstract : Introduction: Problems with team assembly, co-ordination and hierarchy are common in ad-hoc resuscitation teams. These problems can contribute to poor outcome. We developed a short simulation-based training intervention to improve leadership and team working within ad-hoc multidisciplinary teams. Methods: Multidisciplinary groups of 4–6 participants attend a 90 min training session integrated into the working day. A model for effective team working is presented and specific communication and leadership skills demonstrated. This is followed by a simulated peri-arrest scenario and debrief with team members introduced in an ad-hoc manner to allow practice of newly introduced skills. Pre and 6 weeks post intervention knowledge outcomes were assessed by questionnaire. Team working and Leadership attitudes were assessed using a modified Operating Room Management Attitudes Questionnaire (ORMAQ) 1 and analysed using the Mann Whitney U test. Results: 127 participants completed the training intervention; 54% Foundation trainees, 33% Nursing, 13% Anaesthetic or Medical Registrar. There was a significant improvement in self-assessed understanding of team working, leadership, graded assertiveness, SBAR, closed loop communication and shared mental models (p<0.0005). The cohort demonstrated an increase in assertiveness, flattening of hierarchical views and increased willingness to take the lead post intervention. Selected items from the ORMAQ can be see in Table 1. Conclusion: Following the intervention participants had improved understanding of teamworking and leadership skills. There was an increase in assertiveness that enabled participants to raise concerns more easily, speak up and take on more leadership roles. Reference: . Schaefer H, Helmreich R. The Operating Room Management Attitudes Questionnaire (ORMAQ ) (NASA/University of Texas FAA Technical Report) 1993. Austin: University of Texas.